The Influence of Social Environment on Arabic Language Acquisition of Students at Nurul Haramain Islamic Boarding School - Hamdani, Muhammad; Mukarromah, Aenullael; Mahsur, Mahsur; Kamariah, Kamariah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study aims to explore the impact of the social environment on Arabic language acquisition among students at Nurul Haramain Islamic Boarding School. The social environment includes interactions with teachers, peers, and the practice of using Arabic in daily activities within the pesantren. This research employs a descriptive qualitative approach using observation, interviews, and documentation methods. The findings reveal that the social environment significantly contributes to improving students' Arabic language skills, both in comprehension and communication. An environment that encourages active use of Arabic has proven effective in helping students achieve higher language competence. Moreover, support from peers and teachers also plays a crucial role in strengthening learning motivation and fostering positive language habits. In conclusion, a supportive social environment has a substantial impact on the process of Arabic language acquisition among students. تهدف هذه الدراسة إلى استكشاف أثر البيئة الاجتماعية في اكتساب اللغة العربية لدى طلاب مدرسة نور الحرمين الإسلامية الداخلية. تتضمن البيئة الاجتماعية التفاعلات مع المعلمين والأقران وممارسة استخدام اللغة العربية في الأنشطة اليومية داخل المدارس الداخلية. يستخدم هذا البحث المنهج الوصفي النوعي باستخدام أساليب الملاحظة والمقابلات والتوثيق. وأظهرت النتائج أن البيئة الاجتماعية تساهم بشكل كبير في تحسين مهارات اللغة العربية لدى الطلاب، سواء في الفهم أو التواصل. لقد أثبتت البيئة التي تشجع الاستخدام النشط للغة العربية فعاليتها في مساعدة الطلاب على تحقيق كفاءة لغوية أعلى. علاوة على ذلك، يلعب الدعم المقدم من الأقران والمعلمين أيضًا دورًا حاسمًا في تعزيز دافعية التعلم وتعزيز العادات اللغوية الإيجابية. وفي الختام فإن البيئة الاجتماعية الداعمة لها أثر كبير في عملية اكتساب اللغة العربية لدى الطلاب.